Budaya Praktik Pemberian Makanan Pendamping ASI pada Anak Stunting di Bawah Usia Dua Tahun - Suminar, Ratna; Fatimah, Siti; Karim, Fatmawati (Badan Kemitraan Inovasi dan Kewirausahaan Universitas Galuh, 2024)
This systematic review examined the relationship between complementary feeding practices and the prevalence of stunting among children under 24 months. Drawing on a diverse range of studies, in the last 10 years (2013-2023) the review investigated the local cultural conditions, and complementary feeding practices factors influencing stunting. Methods involved synthesizing data from various contexts to identify patterns and associations between the culture, complementary feeding practices, and stunting prevalence. This study carried out a systematic review of journals using two academic databases (PubMed, and Google Scholar) with a publication range from 2013 to 2023. The journal-reviewed guidelines used Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. Results revealed a significant relationship between the local cultural conditions, complementary feeding, and the impact of stunting on child development. This study found 10 studies exploring the relationship between the local cultural conditions, complementary feeding, and the prevalence of stunting among children under 24 months in the last 10 years. The review underscored the need for interventions targeting cultural determinants of stunting and complementary feeding. In conclusion, this systematic review of 10 journals explored the relationship between the local cultural conditions, complementary feeding practices, and the prevalence of stunting among children under two years old in the last 10 years offers. The study elucidated the multifaceted nature of stunting, influenced by cultural beliefs, and complementary feeding practices. The findings emphasized the importance of culturally sensitive interventions aimed at educating parents on proper complementary feeding practices to prevent stunting, particularly in communities where cultural beliefs shape complementary feeding habits. In addition, this observation underscored the importance of addressing contextual factors such as the mother's knowledge of complementary feeding, and the food diversity given, so that there are no food taboos whose nutrients the child's body needs for growth the time to start complementary feeding, and hygiene during complementary feeding processing. It is necessary to emphasize sensitive interventions in solving the stunting problem so that stunting can be resolved comprehensively.